Microbial diversity in acidic anaerobic sedimentsat the geothermal Caviahue-Copahue system, Argentina - Willis Poratti, Graciana (2013)
The microbial diversity of sediment in the acidic Agua del Limón hot spring (located in the geothermal Caviahue-Copahue area, Argentina) was investigated using a combination of molecular and cultivation techniques, with particular emphasis on indigenous anaerobic prokaryotes. Bacteria involved in the iron (Acidithiobacillus ferrooxidans and Leptospirillum spp.) and sulfur (Acidithiobacillus spp., Thermotogales-like bacteria, Thiomonas sp., and Desulfurella sp.) cycles were identified in the clone library. Although no obvious sulfate-reducing bacteria were detected by culture-independent techniques, several isolates related to the mesophilic, sporeforming sulfate-reducer "Desulfobacillus acidavidus" strain CL4 were isolated on solid media incubated at both 30°C and 40°C. The 16S rRNA gene of another isolate showed 94% similarity to Desulfotomaculum thermobenzoicum. Enrichment cultur